Kinneyia: A Flow-Induced Anisotropic Fossil Pattern from Ancient Microbial Mats - Herminghaus, Stephan; Thomas, Katherine Ruth; Aliaskarisohi, Saeedeh; Porada, Hubertus; Goehring, Lucas (Frontiers in Materials, 2016)
Kinneyia is the commonly-used term to describe a class of trace fossil that is strongly associated with microbial mats. The appearance of Kinneyia (or wrinkle-structures) in the fossil record has recently led to a number of possible mechanisms being proposed to explain its formation. Here we outline, and critically compare, three of these models, involving formation of the characteristic ripple-structures (i) in mats over liquefied sediment, (ii) by oscillatory flow of microbial aggregates, and (iii) by a Kelvin-Helmholtz instability of the mat surface. Of these models, our study shows that the hydrodynamic instability compares most favorably with the corresponding structures in the fossil record. Implications for the conditions under which the fossils formed are then further discussed.